A natureza artificial do teatro: Diderot e os paradoxos - Araujo, Carolina Ribeiro Paraíso (2016)
The purpose of this dissertation is to present the importance of the theatre according to Denis Diderot point of view. Thus, based on his thoughts, try to understand the purposes of which, the philosopher will demonstrate from the representative act, in France during the 18th century. Diderot suggests an improvement in the way of making theatre, as well as in its own theatrical representations. The philosopher will determine a theory for the actors to improve their performances. The performances should be based on nature observation, aiming to be studied and represented with pure rationality. In this regard, he gives emphasis to artificiality in disadvantage of nature to create perfection in a scene. In Diderot’s point of view, the theatre should be and do the job of remove society’s addictions and make people work on their virtue. In addition, theater plays should approach people’s busy lives and through that he suggests and introduces a new genre called drama and it is a genre that can be classified as intermediate, being in between tragedy and comedy